2019
DOI: 10.1210/jc.2019-00340
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Turner Syndrome and the Influence of Growth Hormone Therapy: A 20-Year Follow-Up

Abstract: Context The factors that affect the health-related quality of life (HRQoL) of women with Turner syndrome (TS) are controversial. Objective The aim was to describe the HRQoL of women with TS with a focus on how given GH treatment and comorbidity influence HRQoL in adulthood and to compare HRQoL of women with TS with that of women in the general population. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…When considering determinants for these results, we found that especially having comorbidities such as diabetes and orthopaedic complaints were related to lower HR‐QoL. This impaired quality of life was reported before, in which at least some domains of QoL were found to be decreased in women with TS . However, three studies found QoL in women with TS to be comparable to non‐TS controls, or found even better scores by women with TS on some aspects such as social and emotional functioning .…”
Section: Discussionmentioning
confidence: 48%
“…When considering determinants for these results, we found that especially having comorbidities such as diabetes and orthopaedic complaints were related to lower HR‐QoL. This impaired quality of life was reported before, in which at least some domains of QoL were found to be decreased in women with TS . However, three studies found QoL in women with TS to be comparable to non‐TS controls, or found even better scores by women with TS on some aspects such as social and emotional functioning .…”
Section: Discussionmentioning
confidence: 48%
“…This impaired quality of life was reported before, in which at least some domains of QoL were found to be decreased in women with TS. 26,[30][31][32][33][34][35][36] However, three studies found QoL in women with TS to be comparable to non-TS controls, [37][38][39] or found even better scores by women with TS on some aspects such as social and emotional functioning. 38 Our study further determined in which domains Turner patients are especially experiencing difficulties and which factors contributed to their reduced mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other tests and summary tools, transfer records, and a recommended approach for transitioning into adult practice are available on the Endocrine Society website (http://www.endocrinetransitions.org). Hence, multidisciplinary centers have already been established in the Netherlands, UK, Sweden, and in France, resulting in a better quality of the care available to women with TS including organized transition (26, 29, 31, 32, 35). Austria, like Germany, is far behind these developments (2).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors also attribute the insufficient care to a lack of the necessary personal responsibility resulting from the described impairment in social skills displayed by TS patients as a contributing factor (21, 25). Multidisciplinary centers capable of managing the care after childhood are important to improve and maintain the quality of medical care in women with Turner syndrome and were established in several countries during the last decade (26, 27, 28, 29, 30, 31, 32).…”
Section: Introductionmentioning
confidence: 99%